2012
DOI: 10.1136/bmj.e5605
|View full text |Cite
|
Sign up to set email alerts
|

Low glycaemic index diet in pregnancy to prevent macrosomia (ROLO study): randomised control trial

Abstract: Objective To determine if a low glycaemic index diet in pregnancy could reduce the incidence of macrosomia in an at risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
366
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(378 citation statements)
references
References 36 publications
4
366
3
5
Order By: Relevance
“…On the other hand, if overweight women or women with previous macrosomia had been recruited to the trial, the heterogeneity of the study group would have been increased markedly. This could also have had effects on the intervention results (24,26,28,29). We believe that in the RADIEL we have been able to identify a real high-risk group that is also the most likely to benefit from a lifestyle intervention during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, if overweight women or women with previous macrosomia had been recruited to the trial, the heterogeneity of the study group would have been increased markedly. This could also have had effects on the intervention results (24,26,28,29). We believe that in the RADIEL we have been able to identify a real high-risk group that is also the most likely to benefit from a lifestyle intervention during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation is the high-risk status of the women recruited to the study. In several previous GDM and other lifestyle intervention studies during pregnancy (21)(22)(23)(24)26,28,29), the women recruited were only at a modest risk for the development of GDM. This kind of study setting would need a bigger sample size to reveal the effect of a lifestyle intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…88 A low glycaemic index diet in pregnancy appears to have a significant positive effect on gestational weight gain and maternal glucose intolerance, although it does not reduce the incidence of large-for-gestational-age infants in women at risk for fetal macrosomia (having previously delivered an infant weighing more than 4 kg). 89 However, a low glycaemic index diet intervention in pregnancy was found to have a beneficial effect on neonatal central adiposity. 90 According to the NICE (National Institute for Health and Care Excellence) guidelines, pregnant women should base their meals on starchy foods, eat at least five portions of vegetables and fruits each day and consume fibre-rich foods instead of foods rich in fat and sugar.…”
mentioning
confidence: 99%
“…However, some studies have reported no such associations between maternal 25OHD and offspring health [18][19][20][21][22][23]. The aim of this study was to examine the association between maternal and neonatal 25OHD levels and infant size and adiposity at birth, 6-9 months and 2-2.5 years of age in a cohort from the ROLO (Randomised cOntrol trial of LOw glycaemic index diet versus no dietary intervention to prevent recurrence of fetal macrosomia) study [24]. In a previous analysis of a subgroup of the ROLO study, late maternal 25OHD above the cohort median was associated with significantly greater neonatal length than late maternal 25OHD below the median [25].…”
Section: Introductionmentioning
confidence: 99%